Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray pada Mata Pelajaran Ilmu Pengetahuan Sosial di Sekolah Dasar - Irfan Hilman (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2017)
Abstract. Cooperative learning according to some experts useful to grow the capability to work together and help friends. In the cooperative learning students actively involved in the learning process so that a positive impact on the quality of the interaction and communication quality can motivate students to improve school results. Research method used in this research is the method of the experiment facades (quasi experiment). Samples in this research amounted to 40 students for the class to Va and Vb. Divided into class experiment 20 students and control classes 20 students. The results of the study showed that significant difference between the value before we learn (pretes) with the value after learning (postes). Study results after getting the implementation of cooperative learning model model stay two stray (TSTS) greater than before treatment. Based on the results of research can be advanced that cooperative learning Model TSTS types better than conventional method both seen from the social skills and learning results. Recommendation from the results of this research are two types of cooperative learning model TSTS can be an alternative learning model in Social Studies lessons to the object other topics. Key Words: cooperative model, model two stay two stray, learning results, social skills.